The thought of Augusto Del Noce on contemporary society and its political consequences: A critique of the affluent society (Res Publica. Revista de Historia de las Ideas Políticas, 2024)
Augusto Del Noce is one of the thinkers who has been most influential in trying to understand contemporary society, especially since the end of the Second World War. The originality of his analysis lies especially in his explanation of the genesis of the present society and in his characterisation of it. This paper aims to present his ideas in relation to those of other philosophers who largely agree with him. From such an exposition, it is possible to draw the political consequences of his social thought